Analysis of Career Development and Competence on Employee Performance through Job Satisfaction - Munanda; Mesra B; Elfitra Desy Surya (International Journal of Management, Economic and Accounting, 2026)
This study aims to examine the effect of career development and competence on employee performance through job satisfaction as a mediating variable at PT Permodalan Nasional Madani (PNM) Medan Branch. The study employed a quantitative approach with an explanatory research design. The population consisted of 50 employees, and all members of the population were selected as respondents using a saturated sampling (total sampling) technique. Data were collected through a structured questionnaire using a five-point Likert scale and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. The results indicate that career development has a positive and significant effect on job satisfaction with a path coefficient of 0.398, while competence also has a positive and significant effect on job satisfaction with a path coefficient of 0.342. Job satisfaction was found to have a positive and significant effect on employee performance with a path coefficient of 0.401. Furthermore, career development and competence directly and significantly influence employee performance with path coefficients of 0.236 and 0.287, respectively. The mediation analysis revealed that job satisfaction partially mediates the relationship between career development and employee performance, as well as the relationship between competence and employee performance. The R-square value of 0.521 indicates that career development and competence explain 52.1% of the variance in job satisfaction, while the R-square value of 0.612 indicates that career development, competence, and job satisfaction explain 61.2% of the variance in employee performance. The findings imply that improving employee performance can be achieved through strengthening career development programs, enhancing employee competencies, and continuously fostering job satisfaction. This study also reinforces the role of job satisfaction as an important psychological mechanism linking human resource management practices to employee performance improvement.